2016
DOI: 10.4055/cios.2016.8.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Irreducible Anterior Dislocation of the Shoulder without Significant Functional Deficit

Abstract: Shoulder dislocation is frequently encountered by orthopedists, and closed manipulation is often sufficient to treat the injury in an acute setting. Although most dislocations are diagnosed and managed promptly, there are rare cases that are missed or neglected, leading to a chronically dislocated state of the joint. They are usually irreducible and cause considerable pain and functional disability in most affected patients, prompting the need to find a surgical method to reverse the worsening conditions cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…All patients who underwent surgical treatment complained of severe pain, limited activity, and declined quality of life. Though very few cases reported that patients with chronic irreducible anterior dislocation were without significant functional deficit 5 , most cases underwent surgical treatment to maintain patients' active lifestyle, including weightlifting and manual work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients who underwent surgical treatment complained of severe pain, limited activity, and declined quality of life. Though very few cases reported that patients with chronic irreducible anterior dislocation were without significant functional deficit 5 , most cases underwent surgical treatment to maintain patients' active lifestyle, including weightlifting and manual work.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons of neglected shoulder dislocations in younger patients are almost always alcoholism, seizures, or multiple traumas 3, 4 . Though one study reported that the chronic anterior dislocation did not affect the function of the dislocated shoulder 5 , most patients with chronic anterior dislocation were unable to return to normal activities 6, 7 . Chronic anterior shoulder dislocation is commonly associated with several associated injuries, such as Hill–Sachs or Bankart lesions, glenoid fracture, massive glenoid bone loss, rotator cuff tears, or proximal humeral fractures 2, 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, excessive and unnecessary treatment, whether by arthroscopic or open techniques, may cause more harm than good. In some patients of advanced age, a very small number of patients with old shoulder dislocations remain asymptomatic and reasonably functional (19), and this article should remind us that in a very small number of patients, no treatment may be the best treatment.…”
Section: Discussionmentioning
confidence: 97%
“…8 The chance of repositioning the joint by closed manipulation diminished considerably over time, while complications associated with closed reduction substantially increase due to fibrotic soft tissues. 9 Following an unsuccessful attempt of closed reduction, open reduction is the next step. Release of capsule and other soft tissue is necessary to reduce the joint without tension.…”
Section: Discussionmentioning
confidence: 99%